A coupled CFD/Multibody Dynamics analysis tool for offshore wind turbines with aeroelastic blades - Liu, Yuanchuan; Xiao, Qing; Incecik, Atilla (2017)
Aero-elasticity is an important issue for modern large scale offshore wind turbines with long slender blades. The behaviour of deformable turbine blades influences the structure stress and thus the sustainability of blades under large unsteady wind loads. In this paper, we present a fully coupled CFD/MultiBody Dynamics analysis tool to examine this problem. The fluid flow around the turbine is solved using a high-fidelity CFD method while the structural dynamics of flexible blades is predicted using an open source code MBDyn, in which the flexible blades are modelled via a series of beam elements. Firstly, a flexible cantilever beam is simulated to verify the developed tool. The NREL 5 MW offshore wind turbine is then studied with both rigid and flexible blades to analyse the aero-elastic influence on the wind turbine structural response and aerodynamic performance. Comparison is also made against the publicly available data.